Perbandingan Bobot Akhir, Bobot Karkas dan Persentase Karkas Berbagai Strain Broiler - Dede Risnajati (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2012)
The objective of the research was to comperative the final weight, carcass weight and carcass percentages of some broiler strains and and to know the strain that produced the highest final weight, carcass weight and percetage. The research method was survey with design based on Completely Randomized Design. The three strains of broilers were Hybro, Cobb and Hubbard. At 5 weeks old, the chicken were picked up from broiler farms which had the same management. Each was replicated 9 times. Parameters observed were final and carcass weight and carcass percentage. Collected data were analyzed by analysis of variance. The observed strains had no significant difference on final weight, carcass weight and carcass percetages.